Measurement Invariance of Expectations Toward Sustainable Public Transport Service Quality Among Urban and Rural Older Adults - Chantaratang, Anon; Chonsalasin, Dissakoon; Wisutwattanasak, Panuwat; Watcharamaisakul, Fareeda; Champahom, Thanapong; Ratanavaraha, Vatanavongs; Jomnonkwao, Sajjakaj (Civil Engineering Journal, 2025)
This study examines measurement invariance of expectations toward sustainable public transport service quality between urban and rural older adults in Thailand. Using second-order confirmatory factor analysis, data were collected from 1,189 elderly respondents across Thailand's four major regions through face-to-face interviews. The measurement framework incorporated eleven service quality dimensions: nine traditional attributes (Vehicle, Bus Stop, Accessibility, Convenience, Information, Staff, Safety and Security, Reliability, and Affordability) and two extended dimensions (Older's Facilities and Post-Pandemic Prevention). Results demonstrated successful measurement invariance, confirming that the eleven-factor structure operates equivalently across urban and rural contexts. Universal priorities emerged for Convenience, Staff quality, and Reliability, while rural elderly showed elevated importance for Safety and Security. The validation of Older's Facilities and Post-Pandemic Prevention as distinct dimensions establishes empirical support for incorporating age-inclusive design and health protection measures as permanent components of sustainable transport planning, justifying unified national standards while accommodating regional variations for Thailand's aging population.